Transcatheter Self-Expandable Aortic Valve (Portico) Implantation in a Patient with Previous Mitral Valve Replacement: A Case Report - Korkmaz, Ahmet (J Tehran Heart Cent, 2019)
Transcatheter aortic valve implantation (TAVI) has shown favorable outcomes in patients with severe symptomatic aortic valve stenosis who are at high surgical risk or who are unsuitable candidates for open-heart surgery. However, concerns exist over treating patients who have undergone previous mitral valve surgery due to the potential interference between the mitral prosthetic valve or ring and the TAVI device. In this case report, we present a case in which a patient with symptomatic severe aortic stenosis and previous mechanical mitral valve replacement was successfully treated with TAVI using a Portico valve, which is under-researched.